Current Crisis of Human Resource of Health in African Countries - Patel, Kinjal H; Patel, Prakash (National Journal of Community Medicine, 2017)
One of the pillars for successful health care system is efficient health workers. They are also crucial in preparation for response to health threats like emerging epidemics and pandemics like SARS, Avian flu, CCHF, EBOLA, etc. Therefore human resource crisis is seen as the greatest hurdle in achieving basic health needs like childhood immunization, safe pregnancy and delivery, access to prevention and treatment of life threatening disease like HIV/AIDS Malaria and Tuberculosis.